Water-based conductive heating slurry as well as preparation method and application thereof
The aqueous conductive heating slurry with treated graphene and carbon nanotubes addresses precipitation and environmental issues, offering improved conductivity and extended lifespan for heating applications.
Patent Information
- Application Number
- CN202411165676.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-20
AI Technical Summary
Existing conductive heating pastes face issues such as metal powder precipitation, environmental pollution from organic solvents, complex preparation processes, bubbles, pinholes, and short lifespan due to graphene layer folding and agglomeration.
Aqueous conductive heating slurry composed of treated graphene, carbon nanotubes, and conductive carbon black, with a cross-linked structure formed by a curing agent, enhancing conductivity and stability.
The slurry provides good storage stability, conductivity, and long lifespan with reduced environmental impact, suitable for heating electronic products.
Smart Images

Figure BDA0005007809300000081 
Figure BDA0005007809300000091 
Figure BDA0005007809300000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of conductive heating materials, and in particular relates to a water-based conductive heating slurry and a preparation method and application thereof. Background Art
[0002] At present, the main conductive heating pastes on the market are mainly oil-based conductive heating pastes and composite metal conductive ink pastes. Among them, the conductivity of composite metal conductive ink pastes increases with the increase of metal powder dosage, but the density of metal powder is relatively large, easy to precipitate, and inconvenient to use. In addition, organic solvents are mostly used in existing conductive heating pastes, which have VOC emissions during use, and organic solvents are also used when cleaning equipment, causing certain pollution to the environment.
[0003] CN112188660A discloses a water-based graphene-based electric heating film and a preparation method thereof. The film is prepared by dispersing graphene as flake graphite for 8 hours, which takes a long time and is costly. Moreover, the conductive material is only graphene, and graphene has a layer structure that is easy to fold and accumulate to form holes or gaps, resulting in poor conductivity and short life. CN112738929A discloses a water-based electric heating film and a preparation method thereof. This method requires pre-coating of hot melt adhesive on the surface of the substrate. After the electric heating coating is coated and dried, the temperature is further raised to a temperature above its softening point. The nano-conductive carbon material in part of the conductive carbon layer can be directly embedded in the hot melt adhesive by utilizing its softening, adsorption and embedding effect to form a close bond with the substrate. The process is complicated. When the conductive filler is directly coated on the hot melt adhesive, the fluidity of the conductive filler deteriorates, and the bubbles generated by printing burst during the drying process. The conductive filler cannot flow and fill, resulting in pinholes, which affects the quality.
[0004] Therefore, the conductive heating pastes currently on the market mainly have the following problems: metal conductive heating pastes are easy to precipitate, the electric heating film of oily conductive ink is easy to pollute the environment, the electric heating film of water-based conductive heating paste has defects such as complex preparation process, bubbles and pinholes, short life, etc., all of which cannot meet the use requirements. Summary of the invention
[0005] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide an aqueous conductive heating slurry.
[0006] A second object of the present invention is to provide a method for preparing an aqueous conductive heating slurry.
[0007] The third object of the present invention is to provide application of the above-mentioned aqueous conductive heating paste in heating electronic products.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides an aqueous conductive heating slurry, comprising the following raw materials in parts by mass: 1-2 parts of treated graphene, 1-3 parts of carbon nanotubes, 2-5 parts of conductive carbon black, 15.5-24.5 parts of aqueous resin, 0.4-0.8 parts of dispersant, 0.1-0.3 parts of defoaming agent, 0.2-0.6 parts of curing agent, and 20-40 parts of water; the treated graphene is obtained by heat treating graphene at 1000-1200°C in an inert atmosphere.
[0010] In the present invention, during the heat treatment of graphene, impurities and volatile components in the graphene are discharged, and the carbon two-dimensional structure in the graphene is rearranged, so that the purity of the graphene is higher and the microstructure is changed, thereby significantly improving the conductivity of the treated graphene, and further improving the conductivity of the conductive heating paste containing the treated graphene. In addition, the treated graphene in the present invention can effectively absorb and re-radiate infrared light, thereby achieving the function of heating, and the reason is that the electron energy level in the energy band structure of the treated graphene is suitable for the energy of infrared photons, resulting in electron transitions in the energy band, thereby generating infrared radiation.
[0011] The treated graphene used in the present invention is in the form of flakes, the carbon nanotubes are in the form of lines, and the conductive carbon black is in the form of dots. The three conductive powders of different shapes are mixed to cross, fill and support each other. On the one hand, it can prevent the agglomeration and precipitation between the particles in the water-based conductive heating slurry of the present invention, and extend the shelf life of the water-based conductive slurry; on the other hand, it can make the formed conductive heating coating tighter. The addition of the blocked curing agent releases the isocyanate group as the temperature rises, and reacts with the amino, hydroxyl and carboxyl groups on the water-based resin chain to form a cross-linked structure, thereby improving the hardness and wear resistance of the coating. At the same time, the conductive powder (i.e., the treated graphene, carbon nanotubes and conductive carbon black) is also more tightly cross-linked with the water-based resin, forming a denser conductive network, reducing the attenuation rate, improving the service life performance, and having better conductive properties.
[0012] Preferably, the processed graphene is in the form of flakes.
[0013] Preferably, the carbon nanotubes are linear.
[0014] Preferably, the conductive carbon black is in powder form.
[0015] Preferably, the conductive carbon black is selected from at least one of Ketjen black, acetylene and coke.
[0016] Preferably, the carbon nanotubes are selected from at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0017] Preferably, the inert atmosphere is selected from at least one of nitrogen, argon and xenon. Heat treatment of graphene in an inert atmosphere can prevent high temperature oxidation of graphene.
[0018] Preferably, the dispersant is at least one of an amino-modified copolymer polymer dispersant and a nonionic polymer dispersant.
[0019] Preferably, the amino-modified copolymer polymer dispersant is WF816 from Jiangsu Jintu Chemical Co., Ltd.
[0020] Preferably, the nonionic polymer dispersant is AKN-2070 produced by Foshan Qianyou Chemical Co., Ltd.
[0021] Preferably, the defoaming agent is at least one of a mixture of a non-silicon compound and a fumed silica and a silicon polyether defoaming agent.
[0022] Preferably, the mixture of non-silicon compounds and fumed silica is WX201 produced by Jiangsu Jintu Chemical Co., Ltd.
[0023] Preferably, the silicone polyether defoamer is X101867 from Guangzhou Xinges New Materials Company.
[0024] Preferably, the curing agent is selected from at least one of C68 of Wanjun Chemical and AA-9076D of Suzhou Qingtian New Materials Co., Ltd. The curing agent in the present invention will crosslink and cure with the water-based resin at a temperature above 90-120°C. Therefore, the water-based conductive heating paste in the present invention is not easy to cure at room temperature, which can improve the stability of screen printing and reduce the expansion of the water-based resin when heated, thereby increasing the service life of the formed electric heating film coating.
[0025] Preferably, the graphene has a particle size of 5 to 10 μm.
[0026] Preferably, the heat treatment time is 10 to 20 minutes.
[0027] Preferably, the aqueous resin is an aqueous resin solution, and the pH of the aqueous resin solution is 7-9.
[0028] Preferably, the aqueous resin solution contains hydroxyl groups, carboxyl groups and amino groups.
[0029] Preferably, the aqueous resin solution includes 1-3 parts of aqueous acrylic resin solution, 7-9 parts of aqueous acrylic modified resin solution, 6-8 parts of aqueous polyester resin solution, 1-3 parts of modified aqueous polyester solution, and 0.5-1.5 parts of aqueous polyurethane solution.
[0030] Preferably, the solid content of the aqueous acrylic modified resin solution is 40-55%, and the viscosity measured at 25°C is ≥2000cps; the hydroxyl value is 40-50, and the acid value is 60-70; further preferably, the aqueous acrylic modified resin solution is a product of brand H-122 of Foshan Mangrove Water-based Printing and Coating Materials Co., Ltd., which mainly modifies the hydroxyl and carboxyl groups, has a solid content of 48-50%, a viscosity measured at 25°C is ≥2000CPS, a hydroxyl value of 48, and an acid value of 65.
[0031] Preferably, the aqueous acrylic modified resin solution is obtained by modifying hydroxyl groups and carboxyl groups.
[0032] Preferably, the aqueous polyester resin solution has a solid content of 43-47% and a viscosity of 30-500 cps measured at 25°C; further preferably, the aqueous polyester resin solution is a product of RTERKYD 1560 produced by Changxing Chemical Co., Ltd., having a solid content of 43-47% and a viscosity of 30-500 cps measured at 25°C.
[0033] Preferably, the modified aqueous polyester solution has a solid content of 40-50%, a viscosity of 6000-9000 cps at 25°C, and a hydroxyl content of 5-6%. Further preferably, the modified aqueous polyester solution is RHERI, a brand of Guangdong Runchang Nanxing New Materials Co., Ltd. TM The product of 2081 has a solid content of 45±1%, a viscosity of 6000-9000cps measured at 25°C, and a hydroxyl content of 5.5%.
[0034] Preferably, the aqueous polyurethane solution has a solid content of 40-45%, and a viscosity of 600-1200 cps measured at 25°C; further preferably, the aqueous polyurethane solution is a product of brand SGR-2016W produced by Guangzhou Changhao Trading Co., Ltd., having a solid content of 42% and a viscosity of 600-1200 cps measured at 25°C.
[0035] Preferably, the aqueous acrylic resin solution comprises the following raw materials in parts by mass: 30-40 parts of aqueous solid acrylic resin, 5-10 parts of monoethanolamine, 0.2-0.8 parts of defoaming agent, and 45-65 parts of water.
[0036] Preferably, the aqueous acrylic resin solution is prepared by mixing an aqueous solid acrylic resin (Dongguan Detong New Material Technology Co., Ltd., brand DETO-895), monoethanolamine, a defoaming agent and water.
[0037] Preferably, in the method for preparing the aqueous acrylic resin solution, mixing is performed by stirring.
[0038] Preferably, the aqueous acrylic resin solution has a viscosity of 6000-9000 mPa.s measured at 25°C.
[0039] Preferably, the solid content of the aqueous acrylic resin solution is 30-40%.
[0040] Preferably, the aqueous conductive heating paste is formed into a film by screen printing, which requires the aqueous conductive heating paste to have a high viscosity.
[0041] The second aspect of the present invention provides a method for preparing the aqueous conductive heating paste according to the first aspect of the present invention, comprising the following steps:
[0042] It is made by mixing and grinding various raw materials.
[0043] Preferably, the preparation method comprises the following steps:
[0044] Firstly, water-based resin, dispersant, defoamer, curing agent and water are mixed and ground, and then mixed and ground with treated graphene, carbon nanotubes and conductive carbon black to obtain;
[0045] Further preferably, the preparation method comprises the following steps:
[0046] The aqueous resin, dispersant, defoamer, curing agent and water are firstly mixed and ground at a rate of 400-600 r / min, and then mixed and ground with treated graphene, carbon nanotubes and conductive carbon black at a rate of 900-1500 r / min to obtain the product.
[0047] The third aspect of the present invention provides the use of the aqueous conductive heat-generating slurry described in the first aspect of the present invention in heat-generating electronic products.
[0048] The beneficial effects of the present invention are as follows: the water-based conductive heating slurry of the present invention is compounded with three conductive materials, namely, flaky treated graphene, linear carbon nanotubes and powdered conductive carbon black, to form a mutually cross-entangled structure, and the conductive carbon black is filled into the gaps of the network structure formed by the treated graphene and the carbon nanotubes to avoid the precipitation phenomenon caused by the agglomeration of the conductive carbon black, and to form a complete and closely connected conductive network, thereby enhancing the conductive ability and the density of the conductive coating. Therefore, the water-based conductive heating slurry of the present invention has good storage stability, conductive properties and heating properties.
[0049] The aqueous conductive heating paste of the present invention uses water as an organic solvent, does not generate VOC during use, and can be used to clean equipment and screens, meeting the requirements of safe, green and environmentally friendly production. In addition, when the aqueous conductive heating paste of the present invention is printed on a PET film or a PI film by screen printing, it has good adhesion, more effective in stimulating infrared radiation, long life, slow curing at room temperature, easy to clean, and reduces environmental pollution and waste of resources, and can be applied to heating electronic products such as floor heating, wall heating, heating decorative paintings, and heating eye masks. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a SEM image of the conductive heating paste in Example 1.
[0051] Figure 2 This is an infrared thermal imaging image of the conductive heating paste in Example 1. DETAILED DESCRIPTION
[0052] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0053] The raw material information used in the embodiments of the present invention is:
[0054] Treated graphene: Graphene with a particle size of 5-10 μm is baked at 1200° C. in a nitrogen atmosphere for 15 min, and then cooled to room temperature in the furnace to obtain treated graphene.
[0055] Aqueous acrylic resin solution (DT-01): According to the proportion of 35 parts of aqueous acrylic solid resin (brand name DETO-895, purchased from Dongguan Detong New Material Technology Co., Ltd.), 8 parts of monoethanolamine, 0.5 parts of defoaming agent, and 57 parts of deionized water, each material was weighed, and then stirred at a stirring rate of 1200 r / min for 1 hour to obtain an aqueous acrylic resin solution having a viscosity of 8300 mPa.s at room temperature and a solid content of 35%.
[0056] The water-based acrylic modified resin solution was purchased from Foshan Hongshu Water-based Printing and Coating Materials Co., Ltd. with the brand name H-122. It mainly modifies the hydroxyl and carboxyl groups, has a solid content of 48-50%, a viscosity measured at 25°C of ≥2000CPS, a hydroxyl value of 48, and an acid value of 65.
[0057] The aqueous polyester resin solution was purchased from Changxing Chemical Co., Ltd. with the brand name RTERKYD 1560, a solid content of 43-47%, and a viscosity of 30-500 cps measured at 25°C.
[0058] The modified waterborne polyester solution was purchased from Guangdong Runchang Nanxing New Materials Co., Ltd., with the brand name RHERI TM 2081, solid content is 45±1%, viscosity measured at 25°C is 6000-9000mPa·s, and hydroxyl content is 5.5%.
[0059] The waterborne polyurethane solution was purchased from Guangzhou Changhao Trading Co., Ltd. with a brand name of SGR-2016W, a solid content of 42%, and a viscosity of 600-1200 cps.
[0060] The dispersant is a non-ionic polymer dispersant purchased from Foshan Qianyou Chemical Co., Ltd. with the brand name AKN-2070.
[0061] The defoaming agent is a mixture of non-silicon compounds and fumed silica, purchased from Jiangsu Jintu Chemical Co., Ltd., with the brand name of wx201.
[0062] The curing agent was purchased from Wanjun Chemical with a brand name of C68.
[0063] Example 1
[0064] This example provides an aqueous conductive heating paste, which includes the following raw materials: 64.5g of aqueous acrylic resin solution (DT-01), 252g of aqueous acrylic modified resin solution (H-122), 24g of aqueous polyurethane solution (SGR-2016W), 216g of aqueous polyester solution (RTERKYD 1560), 216g of modified aqueous polyester solution (RHERI TM 2081) 60g, dispersant (AKN-2070) 19.2g, defoaming agent (wx201) 4.8g, curing agent (C68) 12g, deionized water 951g, treated graphene 35.4g, multi-walled carbon nanotubes 60.3g, conductive Ketjen black 95.4g.
[0065] The aqueous conductive heating paste in this example is prepared by a preparation method comprising the following steps:
[0066] Step (1): weigh 64.5 g of aqueous acrylic resin solution (DT-01), 252 g of aqueous acrylic modified resin solution (H-122), 24 g of aqueous polyurethane solution (SGR-2016W), 216 g of aqueous polyester solution (RTERKYD 1560), and 216 g of modified aqueous polyester solution (RHERI TM2081) 60g, dispersant (AKN-2070) 19.2g, defoaming agent (wx201) 4.8g, curing agent (C68) 12g, deionized water 951g.
[0067] Step (2): The components weighed in step (1) are mixed evenly, placed in a mixing cylinder of a sand mill, the mixing cylinder of the sand mill is turned on, the stirring speed is adjusted to 500 r / min and stirring is carried out for 5 minutes.
[0068] Step (3): Weigh 35.4 g of treated graphene, 60.3 g of multi-walled carbon nanotubes, and 95.4 g of conductive Ketjen black.
[0069] Step (4): slowly add the conductive powder weighed in step (3) into the mixing cylinder of the sand mill, start the sand mill, adjust the speed to 1000r / min, and grind for 2 hours to obtain the aqueous conductive heating slurry in this example.
[0070] Example 2
[0071] This example provides an aqueous conductive heating paste, which includes the following raw materials: 64.5g of aqueous acrylic resin solution (DT-01), 252g of aqueous acrylic modified resin solution (H-122), 24g of aqueous polyurethane solution (SGR-2016W), 216g of aqueous polyester solution (RTERKYD 1560), 216g of modified aqueous polyester solution (RHERI TM 2081) 60g, dispersant (AKN-2070) 19.2g, defoaming agent (wx201) 4.8g, curing agent (C68) 12g, deionized water 951g, treated graphene 39.6g, multi-walled carbon nanotubes 67.2g, conductive Ketjen black 107.1g.
[0072] The aqueous conductive heating paste in this example is prepared by a preparation method comprising the following steps:
[0073] Step (1): weigh 64.5 g of aqueous acrylic resin solution (DT-01), 252 g of aqueous acrylic modified resin solution (H-122), 24 g of aqueous polyurethane solution (SGR-2016W), 216 g of aqueous polyester solution (RTERKYD 1560), and 216 g of modified aqueous polyester solution (RHERI TM 2081) 60g, dispersant (AKN-2070) 19.2g, defoaming agent (wx201) 4.8g, curing agent (C68) 12g, deionized water 951g.
[0074] Step (2): The components weighed in step (1) are mixed evenly, placed in a mixing cylinder of a sand mill, the mixing cylinder of the sand mill is turned on, the stirring speed is adjusted to 500 r / min and stirring is carried out for 5 minutes.
[0075] Step (3): Weigh 39.6 g of treated graphene, 67.2 g of multi-walled carbon nanotubes and 107.1 g of conductive Ketjen black.
[0076] Step (4): slowly add the conductive powder weighed in step (3) into the mixing tank of the sand mill, start the sand mill, adjust the speed to 1000 / min, and grind for 4 hours to obtain the aqueous conductive heating slurry in this example.
[0077] Example 3
[0078] This example provides an aqueous conductive heating paste, which includes the following raw materials: 64.5g of aqueous acrylic resin solution (DT-01), 252g of aqueous acrylic modified resin solution (H-122), 24g of aqueous polyurethane solution (SGR-2016W), 216g of aqueous polyester solution (RTERKYD 1560), 216g of modified aqueous polyester solution (RHERI TM 2081) 60g, dispersant (AKN-2070) 19.2g, defoaming agent (wx201) 4.8g, curing agent (C68) 12g, deionized water 951g, deionized water 951g, treated graphene 42.3g, multi-walled carbon nanotubes 71.5g and conductive Ketjen black 112.7g.
[0079] The aqueous conductive heating paste in this example is prepared by a preparation method comprising the following steps:
[0080] Step (1): weigh 64.5 g of aqueous acrylic resin solution (DT-01), 252 g of aqueous acrylic modified resin solution (H-122), 24 g of aqueous polyurethane solution (SGR-2016W), 216 g of aqueous polyester solution (RTERKYD 1560), and 216 g of modified aqueous polyester solution (RHERI TM 2081) 60g, dispersant (AKN-2070) 19.2g, defoaming agent (wx201) 4.8g, curing agent (C68) 12g, deionized water 951g.
[0081] Step (2): The components weighed in step (1) are mixed evenly, placed in a mixing cylinder of a sand mill, the mixing cylinder of the sand mill is turned on, the stirring speed is adjusted to 500 / min and stirring is carried out for 5 minutes.
[0082] Step (3): Weigh 42.3 g of treated graphene, 71.5 g of multi-walled carbon nanotubes and 112.7 g of conductive Ketjen black.
[0083] Step (4): slowly add the conductive powder weighed in step (3) into the mixing tank of the sand mill, start the sand mill, adjust the speed to 1000 r / min, and grind for 2 hours to obtain the aqueous conductive heating slurry in this example.
[0084] Example 4
[0085] This example provides an aqueous conductive heating paste, which includes the following raw materials: 68.8 g of aqueous acrylic resin solution (DT-01), 268.8 g of aqueous acrylic modified resin solution (H-122), 25.6 g of aqueous polyurethane solution (SGR-2016W), 230.4 g of aqueous polyester solution (RTERKYD 1560), and 230.4 g of modified aqueous polyester solution (RHERI TM 2081) 64g, dispersant (AKN-2070) 19.2g, defoaming agent (wx201) 4.8g, curing agent (C68) 12g, deionized water 951g, treated graphene 39.6g, multi-walled carbon nanotubes 67.2g and conductive Ketjen black 112.7g.
[0086] The aqueous conductive heating paste in this example is prepared by a preparation method comprising the following steps:
[0087] Step (1): weigh 68.8 g of aqueous acrylic resin solution (DT-01), 268.8 g of aqueous acrylic modified resin solution (H-122), 25.6 g of aqueous polyurethane solution (SGR-2016W), 230.4 g of aqueous polyester solution (RTERKYD 1560), and 230.6 g of aqueous polyester solution (RHERI TM 2081) 64g, dispersant (AKN-2070) 19.2g, defoaming agent (wx201) 4.8g, curing agent (C68) 12g, deionized water 951g.
[0088] Step (2): The components weighed in step (1) are mixed evenly, placed in a mixing cylinder of a sand mill, the mixing cylinder of the sand mill is turned on, the stirring speed is adjusted to 500 r / min and stirring is carried out for 5 minutes.
[0089] Step (3): Weigh 39.6 g of treated graphene, 67.2 g of multi-walled carbon nanotubes and 112.7 g of conductive Ketjen black.
[0090] Step (4): slowly add the conductive powder weighed in step (3) into the mixing cylinder of the sand mill, start the sand mill, adjust the speed to 1000r / min, and grind for 2 hours to obtain the aqueous conductive heating slurry in this example.
[0091] Comparative Example 1
[0092] The aqueous conductive heat-generating slurry in this example is different from that in Example 1 only in that an equal amount of graphene is used in this example to replace the processed graphene in Example 1.
[0093] Comparative Example 2
[0094] The aqueous conductive heating paste in this example is different from that in Example 1 only in that: in this example, treated graphene is not added, but conductive Ketjen black is used instead of treated graphene, so the amount of conductive Ketjen black used is 130.8 g.
[0095] Comparative Example 3
[0096] The conductive heating paste in this example is a commercially available oil-based conductive ink paste product purchased from Dongguan Suyin Electronic Materials Co., Ltd. Its solvent is an organic solvent, and the conductive filler is only graphene and conductive carbon black.
[0097] Comparative Example 4
[0098] The only difference between the aqueous conductive heat-generating paste in this example and that in Example 1 is that this example does not contain a curing agent.
[0099] Comparative Example 5
[0100] The aqueous conductive heating paste in this example is different from that in Example 1 only in that the amount of deionized water added in this example is 1200 g.
[0101] Comparative Example 6
[0102] The difference between the aqueous conductive heating paste in this example and that in Example 1 is that this example uses an equal amount of modified aqueous polyester solution RHERI TM 2081 replaces the aqueous acrylic resin solution DT-01 in Example 1.
[0103] Comparative Example 7
[0104] The only difference between the aqueous conductive heating paste in this example and that in Example 1 is that an equal amount of aqueous polyester solution RTERKYD 1560 is used in this example to replace the aqueous acrylic modified resin solution H-122 in Example 1.
[0105] Comparative Example 8
[0106] The only difference between the aqueous conductive heating paste in this example and Example 1 is that this example does not contain aqueous acrylic resin solution DT-01 and modified aqueous polyester solution RHERI TM 2081, and replaced with an equal amount of deionized water, so the amount of deionized water added in this example is 1075.5g.
[0107] Performance Testing
[0108] 1. Slurry state test
[0109] 300 g of the aqueous conductive heating pastes in Examples 1 to 4 and Comparative Examples 1 to 8 were taken respectively, and their odor, fluidity (whether they flow down naturally by drawing), and whether they precipitate and become difficult to stir after being placed under natural conditions for 30 days, 60 days, and 180 days were tested. The specific test results are shown in Table 1.
[0110] Table 1 Slurry state test results
[0111]
[0112]
[0113] As shown in Table 1, the aqueous conductive heating slurries in Examples 1 to 4 have no obvious odor, good fluidity and storage stability, and the slurry has not precipitated after being stored for 180 days, that is, the shelf life can reach at least 6 months. The conductive Ketjen black in Comparative Example 2 has a large addition amount, a high oil absorption value, a large material viscosity, is not evenly dispersed, has precipitation, and is difficult to stir; Comparative Example 3 is an organic solvent-based slurry, and the solvent evaporates during the material collection process with a pungent odor; In Comparative Example 5, too much deionized water is added, the viscosity decreases, resulting in slight precipitation, which is relatively difficult to stir; By comparing Comparative Example 6 and Comparative Example 7, it can be seen that the aqueous polyester solution has a high solid content and a high viscosity (viscosity is 15000-20000mpa.s), and its addition amount affects the fluidity of the slurry; the aqueous polyester solution has a low viscosity and is easy to precipitate; the aqueous acrylic resin DT-01 helps to improve the wetting properties of the conductive powder.
[0114] 2. Conductivity test
[0115] The conductive properties of the aqueous conductive heating pastes in Examples 1 to 4 and Comparative Examples 1 to 5 were tested respectively, and the specific testing method was as follows:
[0116] Step (1): screen-print the aqueous conductive heating pastes in Examples 1 to 4 and Comparative Examples 1 to 5 on PET or PI films respectively, with a screen of 200 mesh;
[0117] Step (2): then put it into an oven, bake it at 120°C for 5 minutes to solidify it, and take it out to obtain a conductive coating;
[0118] Step (3): Print silver paste on both ends of the conductive coating, screen 250 mesh (electrode), put it into an oven, bake it at 120°C for 3 minutes to solidify, and then take it out;
[0119] Step (4): measuring the square resistance of the conductive coating;
[0120] Step (5): testing the adhesion of the conductive coating according to the test method described in the national standard GB / T 9286-2021;
[0121] Step (6): packaging the printed film and adhesive film in a packaging machine;
[0122] Step (7): According to the life test method of GB / T8287-2008, the power attenuation is tested at 1.35 times the set temperature, i.e., 75°C, with a continuous power-on time of 360 hours. The power attenuation is required to be ≤10%, i.e., the life reaches 30,000 hours.
[0123] The test results obtained according to the above test method are shown in Table 2 below.
[0124] Table 2 Conductivity test results
[0125]
[0126]
[0127] As shown in Table 2, the water-based conductive heating paste in Examples 1 to 4 can be cured in 5 minutes at 120°C, with a fast curing rate, and the conductive coating formed on the PET substrate and the PI substrate has good conductivity at low temperature, and its square resistance is 20-40Ω / □, and it has good adhesion to the substrate, with an adhesion of level 1, and the power attenuation at 75°C is less than 5%, which has good aging resistance. In Comparative Example 1, untreated graphene is added, and the conductivity is poor; in Comparative Example 2, no graphene is added, the paste is unstable, the printing performance is poor, the square resistance is high, the power attenuation is large, and the life of the electric heating is greatly affected; in Comparative Example 3, the oil-based ink, the attenuation rate meets the test requirements, but is slightly higher than the implementation case; in Comparative Example 4, no curing agent is added, and the water-based resin expands under the condition of long-term power-on heating, resulting in a larger gap between the conductive powders, which has a certain impact on the conductivity and power attenuation, and thus affects the service life; in Comparative Example 5, a large amount of deionized water is added, the storage time is relatively poor, and the power attenuation is slightly higher than that of Example 1.
[0128] The surface morphology of the conductive coating made of the aqueous conductive heating slurry in Example 1 was tested using a scanning electron microscope. The specific test results are as follows: Figure 1 As shown ( Figure 1 is the SEM image of Example 1), Figure 1 It can be seen that graphene is in the form of flakes, carbon nanotubes are in the form of lines, and conductive carbon black is in the form of dots. The three conductive powders of different shapes are mixed to cross, fill and support each other. On the one hand, it can improve the performance of preventing the agglomeration and precipitation of particles in the aqueous conductive heating slurry of the present invention, which helps to improve and extend the shelf life of the aqueous conductive slurry; on the other hand, it can make the formed conductive heating coating tighter and form a denser conductive network. Combined with the test results of Comparative Example 2 and Example 1, the attenuation rate is reduced, the service life performance is improved, and the conductive performance is better.
[0129] 3. Heating performance test:
[0130] The conductive heating coating made of the water-based conductive heating slurry in Example 1 was scanned and tested using an infrared thermal imager. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the conductive heating coating made of the aqueous conductive heating slurry in Example 1 has an average temperature difference of less than 5°C when heating, heats evenly, and the heating temperature is about 75°C.
[0131] In summary, the conductive coating formed by the aqueous conductive heating slurry in the present invention on the low-temperature PET or PT substrate has good conductivity, storage stability and aging resistance. The power attenuation of implementation cases 1-4 is less than 5% after energization for 360 hours at 75°C, and no precipitation is generated after being placed for 180 days. Since the aqueous conductive heating slurry in the present invention uses water as a solvent, there is no VOC emission during use, and the use process is more environmentally friendly and pollution-free.
[0132] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A water-based conductive heating slurry, characterized in that: The invention comprises the following raw materials in parts by mass: 1-2 parts of treated graphene, 1-3 parts of carbon nanotubes, 2-5 parts of conductive carbon black, 15.5-24.5 parts of water-based resin, 0.4-0.8 parts of dispersant, 0.1-0.3 parts of defoamer, 0.2-0.6 parts of curing agent and 20-40 parts of water; the treated graphene is prepared by heat-treating the graphene at 1000-1200° C. in an inert atmosphere.
2. The aqueous conductive heating paste according to claim 1, characterized in that: The conductive carbon black is selected from at least one of Ketjen black, acetylene and coke; And / or, the carbon nanotubes are selected from at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes; And / or, the dispersant is at least one of an amino-modified copolymeric polymer dispersant and a nonionic polymer dispersant; And / or, the defoamer is at least one of a silicone polyether defoamer and a modified silicone defoamer.
3. The aqueous conductive heating paste according to claim 1, characterized in that: The particle size of the graphene is 5 to 10 μm.
4. The aqueous conductive heating paste according to claim 1, characterized in that: The heat treatment time is 10 to 20 minutes.
5. The aqueous conductive heating paste according to claim 1, characterized in that: The aqueous resin is an aqueous resin solution, and the pH of the aqueous resin solution is 7 to 9; And / or, the aqueous resin solution contains hydroxyl groups, carboxyl groups and amino groups.
6. The aqueous conductive heating paste according to claim 5, characterized in that: The aqueous resin solution comprises 1-3 parts of aqueous acrylic resin solution, 7-9 parts of aqueous acrylic modified resin solution, 6-8 parts of aqueous polyester resin solution, 1-3 parts of modified aqueous polyester solution, and 0.5-1.5 parts of aqueous polyurethane solution.
7. The aqueous conductive heating paste according to claim 6, characterized in that: The aqueous acrylic resin solution comprises the following raw materials in parts by mass: 30-40 parts of aqueous solid acrylic resin, 5-10 parts of monoethanolamine, 0.2-0.8 parts of defoaming agent, and 45-65 parts of water.
8. The aqueous conductive heating paste according to claim 7, characterized in that: The viscosity of the aqueous acrylic resin solution measured at 25° C. is 6000-9000 mPa.s.
9. The method for preparing the aqueous conductive heat-generating slurry according to any one of claims 1 to 8, characterized in that: The following steps are involved: It is made by mixing and grinding various raw materials.
10. Use of the aqueous conductive heat-generating slurry according to any one of claims 1 to 8 in heat-generating electronic products.
Citation Information
Patent Citations
Water-based graphene-based electrothermal film and preparation method thereof
CN112188660A
Water-based electrothermal film and preparation method thereof
CN112738929A
Cited By
Water-based graphene heating slurry and preparation method thereof
CN122395763A
